The Inherited Traditional Culture of Automobile Molding DNA Design Research - Song Qiang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Design of automobile modeling DNA is the core that makes enterprises establish a good and unique brand image to win on market. This paper described the definition and meaning of production DNA, also discussed the composition of production DNA and researched the design ideas of production DNA from both macro and micro aspects. Finally, it recommended would research the traditional culture into the past, present and future of three periods, explored the idea of traditional culture that the automobile modeling DNA inherited under these three periods and analyzed with the red flag car as an example. This research provided a guideline to help automotive corporations to implement brand strategies, and helped to design autos with Chinese elements, sense of the times and fashion trends and can perform the modern mental outlook of Chinese people. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2185